The complexity of human subjective experience during binocular rivalry - Yilmaz, Cemre; Pabel, Laura; Kerschenbauer, Elias; Ischebeck, Anja; Sipatchin, Alexandra; Bartels, Andreas; Zaretskaya, Natalia (Neuroscience of consciousness, 2025)
Our subjective experience of the sensory information is rich and complex. Yet, typical cognitive and perception psychology paradigms reduce it to a few predefined discrete categories, like yes/no answers or the Likert scales. In the current study, we examined the complexity of subjective visual experience during binocular rivalry, a major experimental paradigm used to study conscious visual perception and its neural mechanisms. Binocular rivalry occurs when the two eyes are presented with two different images that cannot be fused into a uniform percept. As a result, the conscious perception alternates between the two images with brief transition phases in between. Fifty-two subjects viewed binocular rivalry produced by pairs of stimuli with different visual information (images, orthogonal gratings, or moving dots). After each rivalry period, they indicated how many different transition types they perceived and described their perception of each transition type. Using content analysis, we identified 20 unique categories over all subjects, sessions, and stimuli. On average, participants reported 2–3 unique transition categories for each visual stimulus combination. The categories were consistent for each observer over time but varied across participants and stimulus content. Our results show that perceptual transitions during binocular rivalry appear in different forms and depend on the specific visual stimulus content that induces rivalry. Our findings have implications for neuroimaging studies of binocular rivalry, which may yield different results depending on the exact experience of transitions. They also demonstrate how the complexity of subjective visual experience may be underestimated in traditional perception paradigms.